2007
DOI: 10.1001/jama.298.5.519
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for Depression Symptoms Among Adolescent Survivors of War and Displacement in Northern Uganda

Abstract: Context Prior qualitative work with internally displaced persons in war-affected northern Uganda showed significant mental health and psychosocial problems.Objective To assess effect of locally feasible interventions on depression, anxiety, and conduct problem symptoms among adolescent survivors of war and displacement in northern Uganda. Design, Setting, and ParticipantsA randomized controlled trial from May 2005 through December 2005 of 314 adolescents (aged 14-17 years) in 2 camps for internally displaced p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
441
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 514 publications
(456 citation statements)
references
References 30 publications
12
441
3
Order By: Relevance
“…SMD = standardized mean difference. $ confidence interval estimated from (Bolton et al, 2007). # Dose = total intervention time converted to number of 50 min sessions.…”
Section: Resultsmentioning
confidence: 99%
“…SMD = standardized mean difference. $ confidence interval estimated from (Bolton et al, 2007). # Dose = total intervention time converted to number of 50 min sessions.…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted by Jordan et al (2010) revealed the significant beneficial effects of psychosocial approach in improving social-behavior and resilience as well as reducing aggression and psychological difficulties in youth aged between 11-14 in the situations of ongoing violence in Nepal. Another study conducted by Bolton et al (2007) also reported the effectiveness of group interpersonal therapy in reducing depression symptoms of the adolescents after the war and displacement in Northern Uganda.…”
Section: Adolescent Strength and Difficultiesmentioning
confidence: 96%
“…In order to achieve these goals, psychotherapy is commonly used, especially for the victims who suffer from psychiatric disorders. One commonly used approach of the psychotherapies to help victims after disaster is the psychosocial approach (Bolton et al, 2007;Jordan et al, 2010).…”
Section: Mental Health Interventions For the Surviving Victims After mentioning
confidence: 99%
See 1 more Smart Citation
“…In Uganda, clinical trials of adapted western psychotherapeutic interventions have focused on the impact of group interpersonal therapy on stress symptoms in highly selective samples of children in post-conflict settings (Bolton et al, 2007) and adults in non-conflict settings respectively (Bass et al, 2006).…”
Section: Introductionmentioning
confidence: 99%